2010
DOI: 10.1515/cogl.2010.024
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor in usage

Abstract: This paper examines patterns of metaphor in usage. Four samples of text excerpts of on average 47,000 words each were taken from the British National Corpus and annotated for metaphor. The linguistic metaphor data were collected by five analysts on the basis of a highly explicit identification procedure that is a variant of the approach developed by the Pragglejaz Group (Metaphor and Symbol 22: 1–39, 2007). Part of this paper is a report of the protocol and the reliability of the procedure. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(76 citation statements)
references
References 13 publications
5
70
0
1
Order By: Relevance
“…The scalar system was evaluated on the VU Amsterdam Metaphor Corpus (Steen, et al, 2010) which consists of 200,000 words from the British National Corpus divided into four genres (academic, news, fiction, and spoken; performance on the spoken genre was not evaluated for this task because it consists of many short fragmentary utterances) and manually annotated for metaphor by five raters. Previous evaluations using this corpus (Dunn, 2013b) concluded that prepositions annotated as metaphoric in the corpus should not be considered metaphoric for computational purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scalar system was evaluated on the VU Amsterdam Metaphor Corpus (Steen, et al, 2010) which consists of 200,000 words from the British National Corpus divided into four genres (academic, news, fiction, and spoken; performance on the spoken genre was not evaluated for this task because it consists of many short fragmentary utterances) and manually annotated for metaphor by five raters. Previous evaluations using this corpus (Dunn, 2013b) concluded that prepositions annotated as metaphoric in the corpus should not be considered metaphoric for computational purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The most comprehensive noncomputational study of metaphoric expressions in large corpora (Steen, et al, 2010) found that up to 18.5% of words in the British National Corpus were used metaphorically. This means that metaphorically used words not only have very different interpretations than literally used words, but they are also common enough to pose a significant challenge for computational linguistics.…”
Section: Introductionmentioning
confidence: 99%
“…Biber 2011, Mahlberg 2013, but also more advanced statistical procedures such as multi-dimensional analysis in register variation (e. g., Biber 1988). These measures allow identifying non-coincidental, i. e. statistically significant, associations and frequency clusters (for a quantitative cross-register comparison of metaphor across word classes in English, see Steen et al 2010), and they facilitate quantitative variation perspectives as well as qualitative ones.…”
Section: A New Definition Of Stylementioning
confidence: 99%
“…We evaluated these features in a binary classification task using the VU Amsterdam Metaphor Corpus (Steen, et al, 2010), which consists of 200,000 words from the British National Corpus divided into four genres (academic, news, fiction, and spoken; the spoken genre was not evaluated) and annotated by five linguists. Metaphorically used prepositions have been untagged, as have ambiguously metaphoric sentences.…”
Section: Evaluation Of the Featuresmentioning
confidence: 99%